(untitled) (Eurasian Research Bulletin, 2022)
This article discusses the problems of assessing the effectiveness of the activities of executive authorities both at the country level (the case of Uzbekistan) and at the level of municipalities. The article substantiates the need to form an attitude towards the leading role of the individual as a citizen (consumer or taxpayer) in assessing the activities of economic or state institutions as the main appraiser. The approaches currently used to assess the quality of decisions made by the authorities are analyzed. In addition, here the author tries to give his own assumption about the importance of the evaluation process in general. As stated, the assessment of the activities of state bodies is a multifaceted problem that has not yet been sufficiently studied in theoretical, methodological and practical terms. Achieving the goals set by the system for evaluating the activities of state bodies largely depends on the experience of the bodies and employees responsible for the evaluation system.